Visual quickpro guide Unix advanced - Herborth, Chris (Peachpit, 2005)
If you've mastered the flavors, commands, and technical jargon surrounding Unix, are comfortable working from within the command line, and are now itching to take your Unix skills to the next level, this is the place to start! Using the same task-based teaching style and easy visual approach employed in their best-selling Unix (Visual QuickStart Guide), veteran authors Deborah Ray and Eric Ray do more than just enumerate commands here. In these pages, they show you how to combine and synthesize those commands to take full advantage of all of Unix's functionality. The focus here is on advanced Unix security, networking, and system administration. In addition, the authors take a good, hard look at using the Xwindows system to harness Unix's power in the GUI world. By the time you reach the end of this volume, you'll be solving problems, administering systems, and running Xwindows competently-in short, tapping all of Unix's power.